SONIDO Sdn Bhd / Ahmad Syahmi Haziq Roseli - Roseli, Ahmad Syahmi Haziq (2020)
SONIDO Sdn Bhd is a supplier company which distribute a very handful, useful and affordable product. This company produces compact device which is Silencer that will reduce the noise make from the disturbing area and will make the daily life easier and more comfortable. Today, there are place where they never sleep such as cities, thus it creates noises that can distribute people especially when time to sleep. Therefore, the innovation of our product, Silencer built with the invention of new high technology to be able reduce the noise in a close area. It allows the certain close area in the noise environment to become more quitter for them do to something such as for better sleep. It allowed people to use this product by attach and start without having difficulty to use this product which is friendly user product. Thus, Silencer can help people who live in noise area such as in cities and traveller to be able to reduce the noise in the certain area within their place. overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain, and the channel of distribution in the target market. Firstly, our target market is the people who live in the noise area such as cities.